2011
DOI: 10.1002/micr.20932
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pelvic defect and infection with endoprosthesis exposure by topical negative pressure and irrigation with myocutaneous flap

Abstract: The treatment of wound complications and deep infection after hemipelvectomy is challenging. We describe a 17-year-old woman with Ewing sarcoma in the pelvis who underwent hemipelvectomy and reconstruction with an artificial hip joint and bone cement. After the operation, skin necrosis and deep infection with methicillin-resistant Staphylococcus aureus (MRSA) were observed. Debridement resulted in exposure of the artificial joint and bone cement. Topical negative pressure (TNP) and irrigation successfully erad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Yoshida et al presented a case of a pelvic defect and infection with endoprosthesis exposure. The implant was successfully salvaged by the VAC therapy and a myocutaneous flap . Tan et al reported the results of nine cases of muscle flaps to salvage the exposed implants in calcaneum, tibia, knee, clavicular and spine wounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yoshida et al presented a case of a pelvic defect and infection with endoprosthesis exposure. The implant was successfully salvaged by the VAC therapy and a myocutaneous flap . Tan et al reported the results of nine cases of muscle flaps to salvage the exposed implants in calcaneum, tibia, knee, clavicular and spine wounds.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the negative pressure wound therapy may control the wound infection with the spine instrumentation as well as the other implants in orthopaedic patients . Recently, there was a report on using topical negative pressure therapy followed by a myocutaneous flap transfer to cover an infected wound after hemipelvectomy without removal of the endoprothesis …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It helps to remove excess fluid and debris, decrease tissue bacterial levels, improve tissue perfusion, and promote wound healing by creating a barrier and a subatmospheric pressure . Moreover, recent reports have highlighted the use of NPWT in open fractures, for wounds associated with exposure to implants or hardware, and to assist in wound closure of deep wound infections in combination with flap transfer . Radical debridement and negative‐pressure dressings are useful for stabilizing osteomyelitis wounds prior to resurfacing and reconstruction .…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study has proved decrease of bacteria load of wounds that were treated by VAC . Clinical studies also showed that the gram‐negative bacilli were significantly decreased in wounds and eradicated from the wound with exposure of implant after the wounds were treated by VAC . VAC could make the wounds airtight and isolated from external environment, resulting in forming a low oxygen or hypoxia of wounds, which inhibits bacteria growth.…”
Section: Discussionmentioning
confidence: 99%